2016
DOI: 10.5867/medwave.2016.05.6460
|View full text |Cite
|
Sign up to set email alerts
|

Psychological disorders in adults with inherited cardiomyopathies and Takotsubo syndrome

Abstract: We performed a narrative review about psychological disorders in adults with Takotsubo syndrome and inherited cardiomyopathies. Through the electronic database PubMed and PsycINFO we searched all relevant related manuscripts published between 2000 and 2015. We found twelve studies that explore psychological disorders in Takotsubo syndrome and eight about inherited cardiomyopathies: five enrolled patients with hypertrophic cardiomyopathy, two dilated cardiomyopathy, and one arrhythmogenic right ventricular card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There is a paucity of data in children associating psychiatric disorders with takotsubo cardiomyopathy. However, multiple studies in adults have demonstrated an association between anxiety, depression, or mood disorders with takotsubo cardiomyopathy 5,[17][18][19][20][21] . Emotional or physical stress is a well-established trigger for the development of takotsubo cardiomyopathy 5,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data in children associating psychiatric disorders with takotsubo cardiomyopathy. However, multiple studies in adults have demonstrated an association between anxiety, depression, or mood disorders with takotsubo cardiomyopathy 5,[17][18][19][20][21] . Emotional or physical stress is a well-established trigger for the development of takotsubo cardiomyopathy 5,14,15 .…”
Section: Discussionmentioning
confidence: 99%